Expression of genes involved in nodule development in Datisca glomerata - Marco Guedes Salgado (Stockholm University, 2019)
The dataset shows the statistical analysis organized in a spreadsheet (Microsoft Excel, 2016) with tabs linking to the Figures present in the manuscript. Differences in gene expression were assessed by analysis of variance (ANOVA). Equality of variances was checked by Levene’s test. For equal variances, one-way ANOVA was fitted to log2-transformed 2^(-ΔΔCq) with treatments as fixed term and biological repeats as random effects accounting for dependencies between treatments. To estimate and adjust for pairwise multiple comparisons, a non-parametric post-hoc Tukey HSD test was applied. For unequal variances, a Welch’s pairwise t-test with Holm’s correction was used. For the assay involving the interaction of two factors, a two-way ANOVA was fitted to the data with “treatments” as a fixed factor in the model. Biological repeats accounted for random effects nested under the interaction term. Statistics were calculated in RStudio (R studio team, 2017).
Keywords: 60705 Plant Physiology; Biological Sciences; Biologi